PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI, SISTEM PELAPORAN DAN PARTISIPASI MASYARAKAT TERHADAP AKUNTABILITAS PENGELOLA DANA DESA - Fazriatin Nufus; Usep Siswadi; Firmansyah (Universitas La Tansa Mashiro, 2023)
Village Funds are funds used to finance government administration, implementation of development, community development and empowerment of rural communities with the aim of studying or knowing the effect of Utilization of Information Technology, Reporting Systems, and Community Participation on Accountability of Village Fund Management in Warunggunung District in 2022. This study uses quantitative methods. The population used in this study were 40 respondents in the warunggung sub-district. Sampling using purposive sampling method using primary data, primary data in this study is data in the form of data from the distribution of questionnaires. The research data were analyzed using multiple linear regression analysis method with the help of SPSS version.24. The results of this study found that the Information Technology Utilization Variable partially affected the Accountability of Village Fund Management, partially the Reporting System Variable had an effect on the Accountability of Village Fund Management, and the Community Participation variable had no effect on Village Accountability. Fund Management. and Simultaneously the Variables of Utilization of Information Technology, Reporting Systems and Community Participation have a significant effect on Village Fund Management Accountability.